Porous Ni−Al−O Fabricated by a Facile Hydrothermal Method: Improved Catalytic Performance for the Oxidative Dehydrogenation of Ethane to Produce Ethylene. Issue 26 (11th July 2022) - Li, Dong; Kong, Lian; Fan, Xiaoqiang; Xie, Zean; Xiao, Xia; Zhao, Zhen
Abstract: The oxidative dehydrogenation of ethane (ODHE) to ethylene is a process with many advantages (such as energy conservation and coke resistance). Herein, flower‐like Ni−Al−O catalysts with hierarchical structure and high surface areas were fabricated through a hydrothermal route and were applied to ODHE using O2 as oxidant. Compared with NiO alone, the Al 3+ insertion into NiO matrix not only increases the C2 H4 selectivity by 3–4 times, but also prevents the generation of CO2 and CH4 above 500 °C. At 550 °C, all Ni−Al−O catalysts maintain approximately 50 % ethylene selectivity regardless of Al content. The ethylene yield of 29.5 % with C2 H4 selectivity 55.7 % over Ni−Al0.8 ‐O sample can be reached at 500 °C. Moreover, the Ni−Al0.8 ‐O catalyst presents a good stability and has no loss of activity after 100 h continuous evaluation. The various characterizations were carried out for investigating the nature of as‐prepared Ni−Al−O catalysts with different Al loadings. Experimental results demonstrate that the addition of Al not only affects the structure and texture properties of NiO, but also impacts the reducibility of Ni species and the amount of active oxygen species. It is found that the Al 3+ substitution results in: (1) smaller NiO size; (2) larger specific surface area; (3) weaker reducibility and (4) fewer non‐stoichiometric oxygen species. Therefore, the significant improvement of ethylene selectivity is observed in Ni−Alx ‐O catalysts. Abstract : Porous Ni−Al−O catalysts with different Al/Ni molar ratio have been synthesized using a simple hydrothermal strategy. The substitution of Al 3+ ions not only resulted in the formation of Ni−Al solid solution and smaller NiO particles, but also lead to the better lattice oxygen mobility. Therefore, the C2 H4 selectivity was improved and remained greater than 50 % above 500 °C.